Performance enhancement of salisbury screen microwave absorber using dual-layer frequency selective surfaces (FSS) - Mohamed, Saleh Omar (2013)
This project presents design of Salisbury screen absorber using dual layers of frequency selective surface FSS. By using this design, the Salisbury screen able to provide dual absorbtion bands and this can improve the overall operating bandwidth. The performance improvement is obtained when frequency selective surfaces (FSS) is sandwiched between the outermost 377 V/square resistive sheet and the ground plane. In this project the dimension of the cross dipole FSS has been optimized using different length at different layers of FSS. Each FSS is positioned a quarter wavelength separation from the resistive sheet to provide impedance matching at 377ohm and therefore generating several absorption bands. The simulated result by CST Microwave Studio shows by using this strategy, three distinct absorption bands with bandwidth of 36%, 12 and 16 % centered at 6.6, 9.2 and 13 GHz respectively, this is relatively larger relatively compare to a classical Salisbury screen having the same thickness. The simulated results have been verified in measurement where the FSSs were fabricated on FR4 board over frequency range of 8 to 12 GHz. The results obtained have revealed that there are good agreements between the simulation and measurement results.